"Comparing Australian, British, Canadian, and U.S. Broadcasting: The 1934 Radio Reports Compiled by Australian Broadcasting Commissioner E.M.R. Couchman". Issue 1 (2nd January 2021) - Socolow, Michael J.
Abstract: In 1934, Australian Broadcasting Commissioner E.M.R. Couchman traveled to North America and Europe. While visiting Canada, the United States, and Great Britain, Couchman met with radio executives to research and compile analyses of each nation's broadcasting development. Her final reports offer valuable snapshots of early network radio in national broadcasting's formative era, yet they remain largely uncited in the historiography of radio. This article revisits Couchman's work to present an early and overlooked case study of transnational "entangled media history." Couchman's descriptions and insights provide radio scholars with a valuable primary resource compiled by a pioneering woman in radio.